Measuring mismatch unemployment in the Malaysia labour market - Said, Rusmawati; Jamaludin, Salwaty; Ismail, Normaz Wana; Mohamed Nor, Norashidah; Yong, Chen Chen (Oxford University Press, 2021)
Despite its low unemployment rate, the Malaysia labour market is currently sending signals of mismatch, a misallocation between demand and supply that may occur in the form of educational, skills, geographical, occupational, and industrial mismatches. Failure to identify the right type of mismatches will lead to ineffective policies to solve the unemployment issue. Using matching function, this study aims to calculate the labour mismatch index and measure the contribution of mismatch unemployment to the rise of unemployment rate. Employing various sources of data from the Department of Statistics Malaysia, Ministry of Human Resource Malaysia and Bank Negara Malaysia, this study found the presence of skills mismatch in the Malaysia labour market, with the mismatch index gradually increased from 0.108 in 2007 to 0.273 in 2017. Mismatch unemployment explained at most half of the total observed increase in unemployment rate, signalling severe mismatch in the Malaysia labour market.